Microvesicles and exosomes isolated from murine bone marrow-derived mesenchymal stromal cells primed with p38MAPK inhibitor differentially regulate hematopoietic stem cell function - Pallavi Budgude; Vaijayanti Kale; Anuradha Vaidya (Artificial Cells, Nanomedicine, and Biotechnology)
The signaling mechanisms active within mesenchymal stromal cells (MSCs) influence the composition of microvesicles (MVs) and exosomes (Exos) secreted by them. Previously, we showed that priming MSCs with a p38 pharmacological inhibitor (pMSCs) rejuvenates them and improves their ability to promote ex vivo hematopoietic stem cell (HSC) expansion. This study examined whether pMSCs exerted HSC-supportive ability via MVs (pMVs) and Exos (pExos). Our findings demonstrate distinct regulation of HSC fate by pMVs and pExos. pMVs promoted the expansion of long-term HSCs (LT-HSCs), distinguished by their robust self-renewal capacity and superior engraftment ability. In contrast, pExos facilitated expansion of short-term HSCs (ST-HSCs) with high proliferative and differentiation potential. Infusing a combination of pMVs- and pExos-expanded HSCs as a composite graft resulted in significantly higher HSC engraftment, emphasizing the synergistic interaction between LT- and ST-HSC populations. Gene expression studies, functional and phenotypic experiments showed that pMVs regulate HSC quiescence via the Egr1/Cdkn1a axis, while pExos control HSC proliferation via the Nfya/Cdkn1a axis. These findings provide insights into the molecular mechanisms underlying the differential regulation of HSC function by pMVs and pExos. It also proposes a composite graft strategy of using pMVs and pExos as “MSC-derived biologics” for improving the HSC transplantation success.